Gold(I)-Catalyzed Oriented Assembly of Dihydropyridines - Li, Yufeng; Wu, Zhengguang; Pan, Yi; Huang, Hao; Shi, Jie; Bu, Hongzhong; Ma, Hongfei; Liang, Yingying; Huang, Binbin (Synlett, 2015)
A novel method for the assembly of multisubstitued dihydropyridines has been developed starting from methyl propiolate and propargylamines. The reactions were efficiently catalyzed by AuPPh3Cl to get high regioselectivity and high yields. And alternatively, since propargylamines could be easily derived by the CuCl-mediated addition of methyl propiolate to imines, the reactions could be carried out as a sequential three-component model.
Keywords: triphenylphosphine gold chloride; methyl propiolate; propargylamines; dihydropyridines